G-2964A and C734A genetic polymorphisms of CYP1A2 in Chinese population - Han Xing-Mei; Chen Xiao-Ping; Wu Qi-Nan; Jiang Chang-Hong; Zhou Hong-Hao (Acta Pharmacologica Sinica; Vol 21, No 11 (November 2000): Acta Pharmacologica Sinica, 2016)
"AIM: To observe the G-2964A and C734A genetic polymorphisms of human CYP1A2 in Chinese population. METHODS: Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) was employed in genotyping analysis. RESULTS: The allele frequencies of A-2964 were 0.25 and 0.22 in Qidong and Changsha populations, respectively. The incidences of A734 were 0.68 in Qidong population and 0.66 in Changsha population. No more than two low-inducibility/activity alleles were presented in one person. CONCLUSION: The distribution of the G-2964A and C734A genetic polymorphisms did not show significant difference between Chinese and Japanese populations. The incidence of C734A in Chinese was also similar to that in Caucasian population."